Integrasi kecakapan hidup dalam pembelajaran ipa tema selalu berhemat energi pada peserta didik kelas iv sekolah dasar - Aisyah, Aisyah; Sukarno, Sukarno; Sriyanto, Muhammad Ismail (Didaktika Dwija Indria, 2021)
The purpose of this research is to describe the integration of life skills in science learning theme always save energy in students in grade IV SD Negeri Pajang 4 Surakarta. The research uses descriptive qualitative method with case study approach. Students, teachers and parents of grade IV as subjects. Collection techniques with interviews, questionnaires and documentation studies. Miles and Huberman's analysis is used for data analysis. Validity of data by triangulating techniques and sources. The result of this research is that teachers integrate life skills in science learning themes always save energy on learners. Found four skills, namely personal, social, intellectual and vocational skills that run well. Then there are the obstacles of each teacher's skills and efforts to overcome obstacles by maintaining communication, instilling honesty, tolerance of delays in collecting tasks, looking at the process of student activities and others.